Least-Squares Support Vector Machine and its Application in the Simultaneous Quantitative Spectrophotometric Determination of Pharmaceutical Ternary Mixture: Determination of pharmaceutical ternary mixture - Mofavvaz, Shirin; Sohrabi, Mahmoud Reza; Sahebi Farhad, Shiva; Nezamzadeh-Ejhieh, Alireza (Iranian Journal of Pharmaceutical Sciences, 2018)
This paper proposes the least-squares support vector machine (LS-SVM) as an intelligent method applied on absorption spectra for the simultaneous determination of paracetamol (PCT), caffeine (CAF), and ibuprofen (IB) in Novafen. The signal to noise ratio (S/N) increased. Also, In the LS - SVM model, Kernel parameter (